MODEL INTEGRATED LEARNING DI TINGKAT SD/MI - Muh Haris Zubaidillah (Program Studi PGMI STAI Al Falah Banjarbaru, 2018)
Integrated learning as a process has several characteristics, namely: child-centered, the learning process prioritizes giving direct experience, and the separation between fields of study is not clearly visible. Integrated learning also provides results that can develop according to children's interests and needs. One of the prominent limitations of integrated learning is the evaluation factor. Integrated learning is a learning system that enables students, both individually and in groups, to actively seek, explore and present scientific concepts and principles holistically, meaningfully, and authentically. On the basis of several reasons the integrated learning model is very suitable for elementary school (SD/MI) students, including education in primary schools must pay attention to children's intellectual development. In accordance with the level of development, elementary school (SD/MI) students see the world around them as a whole, they have not been able to separate the study material from one another. Keywords: Integrated Learning, Model, SD / MI